2012
DOI: 10.1002/ajpa.22092
|View full text |Cite|
|
Sign up to set email alerts
|

In poor families, mothers' milk is richer for daughters than sons: A test of Trivers–Willard hypothesis in agropastoral settlements in Northern Kenya

Abstract: Birds such as the cowbird that lay their eggs in the nests of other birds have evolved strategies to disguise their chicks and not just their eggs. María De Mársico and her colleagues at the University of Buenos Aires observed eggs or hatchlings from the screaming cowbird (Molothrus rufoaxillaris; pictured left) or the shiny cowbird (Molothrus bonariensis) that were placed or laid in the nests of the baywing (Agelaioides badius; right), and measured the fledglings' survival rates. The researchers found

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 58 publications
(106 reference statements)
2
95
2
1
Order By: Relevance
“…This relationship has been demonstrated in many species, including humans (Homo sapiens, Powe et al, 2010;Fujita et al, 2012), rhesus macaques (Macaca mulatta, Hinde, 2007aHinde, , 2009) red deer (Cervus elaphus hispanicus, Landete-Castillejos et al, 2005), and tammar wallabies (Macropus eugenii, Robert and Braun, 2012). A common trend in these studies is that milk composition, particularly fat, protein and/or energy density, tends to be higher in the milk of mothers nursing sons than in mothers nursing daughters.…”
Section: Maternal Characteristics and Milk Compositionmentioning
confidence: 90%
“…This relationship has been demonstrated in many species, including humans (Homo sapiens, Powe et al, 2010;Fujita et al, 2012), rhesus macaques (Macaca mulatta, Hinde, 2007aHinde, , 2009) red deer (Cervus elaphus hispanicus, Landete-Castillejos et al, 2005), and tammar wallabies (Macropus eugenii, Robert and Braun, 2012). A common trend in these studies is that milk composition, particularly fat, protein and/or energy density, tends to be higher in the milk of mothers nursing sons than in mothers nursing daughters.…”
Section: Maternal Characteristics and Milk Compositionmentioning
confidence: 90%
“…Recently, Powe et al (2010) and Fujita et al (2012) have reported preliminary evidence for sex-based differences in human milk composition-particularly fat and energy. However, several large prior studies of human milk have not reported differences in the milk composition of mothers nursing male or female infants (Prentice et al, 1981;Nommsen et al, 1991;Mitoulas et al, 2002), either reflecting a lack of findings or investigation.…”
Section: Introductionmentioning
confidence: 98%
“…Suckling behavior, however, is not useful for estimating milk energy transfer as verified by experimental use of radio-labeled isotopes in Equus caballus [22]. Direct evidence for sex-biased milk synthesis among nondomesticated species has now been reported in ungulates (Cervus elaphus hispanicus, [23]), rodents (Myodes glareolus [24]), primates (Macaca mulatta [25][26]; Homo sapiens [27][28][29], but see also [30] for exception), and marsupials (Macropus eugenii, [31]). Drawing systematic conclusions from the studies to date, however, is challenging in part because most have been limited by relatively small sample sizes or report milk composition without accounting for milk yield.…”
Section: Introductionmentioning
confidence: 99%